Measurement report: A comparative analysis of an intensive incursion of fluorescing African dust particles over Puerto Rico and another over Spain - B. Sarangi; D. Baumgardner; A. I. Calvo; B. Bolaños-Rosero; R. Fraile; A. Rodríguez-Fernández; D. Fernández-González; C. Blanco-Alegre; C. Gonçalves; E. D. Vicente; O. L. Mayol-Bracero; O. L. Mayol-Bracero (Atmospheric Chemistry and Physics)
Measurements during episodes of African dust, made with two wideband integrated bioaerosol spectrometers (WIBSs), one on the northeastern coast of Puerto Rico and the other in the city of León, Spain, show unmistakable, bioaerosol-like fluorescing aerosol particles (FAPs) that can be associated with these dust episodes. The Puerto Rico event occurred during a major incursion of African dust during June 2020. The León event occurred in the late winter and spring of 2022, when widespread, elevated layers of dust inundated the Iberian Peninsula. Satellite and back-trajectory analyses confirm that dust from northern Africa was the source of the particles during both events. The WIBSs measure the size of individual particles in the range from 0.5 to 30 µm, derive a shape factor, and classify seven types of fluorescence from the FAPs. In general, it is not possible to directly determine the specific biological identity from fluorescence signatures; however, measurements of these types of bioaerosols in laboratory studies allow us to compare ambient fluorescence patterns with whole microbial cells measured under controlled conditions. Here we introduce some new metrics that offer a more quantitative approach for comparing FAP characteristics derived from particles measured under different environmental conditions. The analysis highlights the similarities and differences at the two locations and reveals differences that can be attributed to the age and history of the dust plumes, e.g., the amount of time that the air masses were in the mixed layer and the frequency of precipitation along the air mass trajectory.